2017
DOI: 10.3390/ijerph14060666
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Pollutants in Porous Asphalt Pavements, Laboratory Experiments to Investigate Their Potential to Impact Environmental Health

Abstract: Pervious Paving Systems (PPS) are part of a sustainable approach to drainage in which excess surface water is encouraged to infiltrate through their structure, during which potentially toxic elements, such as metals and hydrocarbons are treated by biodegradation and physical entrapment and storage. However, it is not known where in the PPS structure these contaminants accumulate, which has implications for environmental health, particularly during maintenance, as well as consequences for the recycling of mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…PPS have been commended by numerous studies [67,74,93,141,142] for the trapping of sediments and other pollutants during infiltration of stormwater runoff. However, this process can result in the clogging of the pavement surface leading to reduced infiltration rates.…”
Section: Cloggingmentioning
confidence: 99%
See 1 more Smart Citation
“…PPS have been commended by numerous studies [67,74,93,141,142] for the trapping of sediments and other pollutants during infiltration of stormwater runoff. However, this process can result in the clogging of the pavement surface leading to reduced infiltration rates.…”
Section: Cloggingmentioning
confidence: 99%
“…[145] In a study conducted on 52 permeable pavement sites, Nichols and Lucke [146] found that particle size distribution (PSD) curves could not be used as a stand-alone tool to infer PICP clogging processes but found that fine particles of sizes 251 to 550 µm contributed to lower infiltration rate measurements. Charlesworth et al [142] found that after three years of monitoring, the majority of the sediments were located in the surface layer of a porous asphalt laboratory test rig.…”
Section: Cloggingmentioning
confidence: 99%
“…These pollutants include suspended solids, organic matter, nutrients, heavy metals, oils and even polycyclic aromatic hydrocarbons (PAHs) [3,4]. To mitigate these negative effects, and potentially start using stormwater as a resource instead of a waste product, low impact development (LID) options such as permeable pavement systems (PPS), are seeing an increase in implementation in low-traffic areas in place of impermeable surfaces [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…They are treated by biodegradation and physical entrapment and stored over the long term; heavy metals are stored inside the structure for the service life of the pavement. Charlesworth et al [36] investigated the potential impacts of released contaminants on the environment and human health during maintenance procedures and found that their accumulation does not imply an environmental pollution risk when carrying out pavement maintenance and rehabilitation work. Moreover, the materials could be recycled at end of life.…”
mentioning
confidence: 99%
“…The capillary network of pedestrian areas distributed throughout the city could have a strategic role in mitigating flood risks. Despite the punctual approach of water squares [36,37] and water retention chambers [38,39], which are large underground storage facilities, a porous pavement offers a continuous and distributed system to manage rainwater.…”
mentioning
confidence: 99%